Bio‐inspired synthesis of AgNPs from lichen as potential antibacterial and mosquito larvicidal activity with negligible toxicity on Gambusia affinis. Issue 4 (9th April 2023) - Loganathan, Kalimuthu; Chellamuthu, Vasugi; Karupuswami, Dhanalakshmi; Mohan, Kannan; Suresh, Udaiyan; Panneerselvam, Chellasamy; Trivedi, Subrata; Aziz, Al Thabiani; Alatawi, Fuad A.; Munshi, Alaa M.; Al‐Aoh, Hatem A.; Al‐Shehri, Hamza S.; et al.
Abstract: Mosquitoes serve as reservoirs for viruses and other microorganisms, posing a significant health‐related issue for both humans as well as livestock. Control of these deadly disease‐producing mosquito vectors is of paramount importance. The chemical analysis of Parmotrema reticulatum was examined by GC–MS. Further, lichen‐mediated AgNPs were confirmed through UV–vis spectrophotometry, FTIR, TEM‐EDX, and XRD. After 24 h post‐treatment, the lichen‐synthesized AgNPs showed considerable toxicity against distinct Aedes aegypti instars with LC50 values of 44.61 (I instar), 51.27 (II instars), 61.34 (III instars), 72.95 (IV instar), and 89.84 (pupae) μg/mL, respectively. Further, both P. reticulatum extract and AgNPs greatly reduced the survival and reproductive efficiency of A. aegypti adults. Eventually, in conventional laboratory circumstances, the predatory effectiveness of Gambusia affinis against Ae. aegypti II and III instar larvae were 71.35% and 53.40%, respectively. In antibacterial assays, low concentrations of the P. reticulatum synthesized AgNPs inhibited the development of Pseudomonas aeruginosa and Citrobacter freundii . Surface damage, ROS production, and protein leakage are the antibacterial mechanisms of AgNPs. Overall, the lichen‐derived AgNPs can be regarded as newer and safer Ae. aegypti control instruments.